Análisis comparativo de los gases residuales de la combustión y fallas en motores Hyundai modelo 9h21/32, en estación de generación eléctrica distribuida - Llanes Cedeño, Edilberto (2017)
The present work was carried on in the maintenance company to generator group fuel-oil (emgef) in bayamo city, granma -cuba. The composition of the gases was selected as indicators of failures in the motors hyundai model 9h21/32 that constitute the emplacement. For the realization of the experiment was used a multifactorial design using like essential factors 16 motors and an operating time of 3 months. Calculation and period analysis of the waste gases of the combustion of the motors hyundai, confirmed to be an effective tool that allows obtaining from the operation in the station a quality assessment. Did not observe differences between the motors analyzing the compositions of carbon dioxide, carbon monoxide, sulfur dioxide, relation co/co2 and combustion efficiency. However, significant differences between the gases nitrogen monoxide and temperature of the gases was observed. The main failures relate to leaks exhaust gas manifold, fuel injection system regulation and gas leaks by the turbocharger.